2010
DOI: 10.1007/s10439-010-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Spreading, and Adhesion Strength of Human Bone Marrow Cells on Chitosan

Abstract: The successful integration of an orthopedic implant into bone depends on the mechanisms at the tissue-implant interface and mostly on the osteoblast attachment phenomenon. Chitosan has emerged as an attractive biomacromolecule favoring osseointegration. In this study highly deacetylated chitosan coatings, with roughness of about 1 nm, were bonded to glass surfaces via silane-glutaraldehyde molecules. Human osteoblasts were used to study the development of attachment during the first 60 min. Chitosan favored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…To this end, we needed a polymer that would be easily functionalized, but also would have intrinsic characteristics favorable to the product end application, as allowing osteointegration, and inhibiting bacterial adhesion and growth. Therefore, we chose chitosan, as it fulfills the characteristics mentioned above, with reported antimicrobial [13][14][15][16] and osteogenic properties [17][18][19][20]. As summarized by us [4], AMP covalent immobilization may result in activity lost, so some parameters should be addressed in order to obtain maximum activity, namely (i) orientation (N-or C-terminal immobilization) and (ii) exposition.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we needed a polymer that would be easily functionalized, but also would have intrinsic characteristics favorable to the product end application, as allowing osteointegration, and inhibiting bacterial adhesion and growth. Therefore, we chose chitosan, as it fulfills the characteristics mentioned above, with reported antimicrobial [13][14][15][16] and osteogenic properties [17][18][19][20]. As summarized by us [4], AMP covalent immobilization may result in activity lost, so some parameters should be addressed in order to obtain maximum activity, namely (i) orientation (N-or C-terminal immobilization) and (ii) exposition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increased metabolic activity and proliferation of MSC with PLGA/CH suggested that the polyblend construct provided more favorable growth and survival conditions for MSC than did PLGA alone. The improved attachment and growth of cells on substrates made from chitosan might be due to the cationic nature of the amine groups in chitosan, which enhances the attraction for negatively charged cells as well [28]. As we grow our MSC in media containing serum it is more likely that cells attach to adsorbed serum proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has been widely used in research for many tissue engineering applications, especially in combination with MSC for bone [28][29][30] (enhancing osteogenesis) and neural tissue engineering [31,32]. Previous studies have shown that MSC cultured on nonfibrous scaffolds composed of PLGA and chitosan facilitate cell viability, proliferation, and adhesion [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research focusing on the surface modification of these materials could considerably increase the success of orthopaedic fixations. Chitosan, the partly deacetylated configuration of chitin, is one of the natural materials under investigation to improve implant integration and cellular attachment [3-5]. Several promising properties are attributed to chitosan, including biocompatibility, non-toxicity and in vivo degradation [6].…”
Section: Introductionmentioning
confidence: 99%